Integrating Collaborative Learning with Polya Problem-Solving Approach: A Model for Critical Thinking that Comprise of Pre-Service Teachers’ Factors - Isaiah Dilor Dookurong; Yarhands Dissou Arthur; Emmanuel Akwertey (Journal of the Indonesian Mathematics Education Society, 2026)
This study examined the effect of integrating collaborative learning with Polya’s problem-solving approach on pre-service teachers’ attitudes, engagement, and critical thinking skills in mathematics. Guided by a pragmatist paradigm, the study adopted a sequential explanatory experimental design. The population comprised pre-service mathematics teachers, from which a purposive sample of 390 participants was selected. Quantitative data were collected at the pretest stage using a critical thinking achievement test and structured questionnaires measuring attitudes and engagement. Both qualitative and quantitative data were collected at the posttest stage through parallel critical thinking achievement test and open-ended responses respectively for classroom-based evidence. Quantitative data were analyzed using descriptive statistics and independent samples t-tests to establish baseline differences between groups, while qualitative data were analyzed thematically following Braun and Clarke’s six-phase approach. The findings indicated that the integrated instructional approach improved pre-service teachers’ attitudes toward mathematics, increased their engagement in learning activities, and enhanced their critical thinking skills. Qualitative evidence further revealed that active collaboration, positive learning dispositions, and sustained participation supported deeper understanding and higher-order thinking. The study contributes to mathematics teacher education by demonstrating how the integration of collaborative learning with Polya’s problem-solving approach can strengthen instructional practices and foster the development of critical thinking among pre-service teachers. The findings provide empirical support for adopting integrated pedagogical strategies that promote engagement and meaningful learning in mathematics classrooms.